2020
DOI: 10.1371/journal.pone.0230515
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal symptoms, physical activity level and quality of life of women living in the Mediterranean region

Abstract: IntroductionThe main purpose of this study is to investigate the relationship between menopause related discomforts and the quality of life of Lebanese women correlated with the physical activity level, anthropometric, medical, sociodemographic and lifestyle variables, during mid-life. Materials and methodsThis cross-sectional study was conducted among 1113 women, recruited from different Lebanese regions. The Menopause-Specific Quality of Life Questionnaire (MENQOL) was used to assess menopause related sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 43 publications
7
41
1
5
Order By: Relevance
“…Likewise, the intensity of menopausal symptoms among Iranian women correlated only with marital status and husbands' level of education [60]. On the contrary, these findings are incongruent with those reported among Jordanian and Lebanese women [9,10] where the severity and occurrence of overall menopausal symptoms correlated with age, family income, level of education, parity, perceived health status, and menopausal status. This discrepancy may be related to the fact that most participants in the current study were postmenopausal, which implies minor differences in variables related to age and health status.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Likewise, the intensity of menopausal symptoms among Iranian women correlated only with marital status and husbands' level of education [60]. On the contrary, these findings are incongruent with those reported among Jordanian and Lebanese women [9,10] where the severity and occurrence of overall menopausal symptoms correlated with age, family income, level of education, parity, perceived health status, and menopausal status. This discrepancy may be related to the fact that most participants in the current study were postmenopausal, which implies minor differences in variables related to age and health status.…”
Section: Discussionmentioning
confidence: 60%
“…The MENQOL scale contains 29 items, which explore the experience of different menopausal symptoms as endorsed or not endorsed as well as the degree of being bothered by symptoms on a scale that ranges from 0 (not at all bothered) to 6 (extremely bothered). Symptoms assessed by the MENQOL are distinguished into four domains: vasomotor (items 1-3), psychosocial (items 4-10), physical (items [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], and sexual (items 27-29) [9,42]. The questionnaire was translated into Arabic by a professional translator.…”
Section: Study Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the former study, more than half of the studied population was smokers, contributing to the significantly lower ANM value. 40 On the other hand, a study in Saudi Arabia disclosed that the ANM was 48.3 ± 3, which was not significantly different than Jordanians, and only 1.8% were smokers. 41 …”
Section: Discussionmentioning
confidence: 90%
“…This measurement is made through the subjective perception of women, which implies for some authors an insurmountable bias, while others extol the virtues of being able to know exactly how women feel. Numerous studies have indicated that mature women achieve worse results on scales that assess quality of life or perceived health than men [5][6][7][8]. Life satisfaction is a key factor in HRQL.…”
Section: Introductionmentioning
confidence: 99%